(untitled) (Revista Brasileira de Contabilidade e Gestão, 2013)
This article discusses the application of artificial intelligence techniques in the software engineering environment. It presents brief conceptual information on intelligent computing and the techniques used in the examined works, focusing on the practical application of each technique. It was based on works already published on the Internet and in the end, it intended to reach a notion of the importance of using artificial intelligence in software engineering and the benefits it can bring.